Narcisizem in obrambni mehanizmi pri ženskah - Bele, Sabina (Psihološka obzorja (Ljubljana), 2014)
The purpose of this research was to examine how the level of covert and overt narcissism is connected to the frequency of the use of defense mechanisms such as denial, repression, regression, projection, compensation, projection, intellectualization, reaction formation, displacement, dissociation, and somatoform dissociation. We can distinguish healthy narcissism, an appropriate self-evaluation, from pathological narcissism, unrealistic self-evalutaion hiding sense of one%s own unworthiness with self-idealization and grandiose thinking. When combined with low/no empathy and exploiting of others, one is diagnosed with narcissistic personality disorder. In this research we focused on narcissism as a personality trait, keeping in mind that we can differentiate between more covert or overt form of narcissism. We also focused on defense mechanisms protecting an individual from stimuli that are either endangering self-esteem or produce anxiety. Although their use is often unconscious, recent findings support the thesis that an individual can observe and report them. Our sample comprised 203 women. We used Narcissistic Personality Inventory, The Hypersensitive Narcissism Scale, The Life Style Index, The Dissociative Experience Scale, and Somatoform Dissociation Questionnaire. Results indicated that women with higher levels of covert narcissism as a personality trait use defense mechanisms, especially regression on earlier developmental stage, compensation deficits on other areas, projection unwanted or unacceptable aspects, reaction formation, and dissociation (absorption, depersonalization and derealization) more often than women with higher levels of overt narcissism. The later use more compensation as a way of dealing with loss, intellectualization as a rational response instead of emotional one, and regression.
Keywords: narcisizem; narcissism; osebnostne lastnosti; personality traits; woman; women; ženske; Narcissistic Personality inventory; Vprašalnik narcizma NPI; psihologija; psychology